Adversity Quotient as a Predictor of Self-Adjustment of Islamic Boarding School Students - Nur Hasan; Fauzul Adim Ubaidillah; Hendri Hendri (LP2M Universitas Ibrahimy, 2024)
Self-adjustment is an effort made by individuals in overcoming problems to harmonize self-pressure and the environment. Meanwhile, the adversity quotient is the intelligence a person has in overcoming difficulties and being able to survive. A person's adversity quotient can be measured by their ability to overcome every problem in life without giving up hope. The method used in this research uses quantitative research methods with a correlational research design. There were 169 participants in this research. Data analysis in this study used a simple regression test. The results of the research show that the adversity quotient is able to predict students' self-adjustment abilities while studying at Islamic boarding schools. Adversity quotient can be an internal aspect of students that can be improved so that students are able to adapt to changing conditions while studying at Islamic boarding schools.